Acute kidney injury in patients with pulmonary embolism: A population-based cohort study - Chang, Chih-Hsiang (Medicine (Baltimore), 2017)
Acute kidney injury (AKI) is overlooked in patients with pulmonary embolism (PE). Risk factors for and long-term outcomes of this complication remain unknown. This study evaluated the predictors and prognosis of AKI in patients with PE. This retrospective cohort study used Taiwan's National Health Insurance Research Database. We enrolled a total of 7588 patients who were admitted to a hospital for PE from January1997 to December 2011 and administered anticoagulation or thrombolytic agents. All demographic data, risk factors, and outcomes were analyzed. AKI was diagnosed in 372 (4.9%) patients. Multivariate logistic regression analysis revealed pre-existing chronic kidney disease, hypertension, diabetes mellitus, massive PE, anemia, and sepsis as independent risk factors for AKI. In the long-term follow-up, the survival rate was similar in the AKI and non-AKI groups. Careful risk factor screening and intensive intervention in patients with AKI might yield outcomes similar to those in patients without AKI.